2015
DOI: 10.1101/lm.038851.115
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability to changes in temporal structure is fornix-dependent

Abstract: Recognition memory deficits, even after short delays, are sometimes observed following hippocampal damage. One hypothesis links the hippocampus with processes in updating contextual memory representation. Here, we used fornix transection, which partially disconnects the hippocampal system, and compares the performance of fornix-transected monkeys with normal monkeys on two versions of a delayed-matching-to-position task with short delays. Spatial recognition memory was affected by fornix transection only when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…By registering each event as it occurs, the hippocampal network continuously tracks the progression of events within an experience. This interpretation of the ongoing neural activity complements research showing that hippocampal lesions impair the ability to monitor recent choices [15,16,50] and to track events across time [11,13,14,20]. …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…By registering each event as it occurs, the hippocampal network continuously tracks the progression of events within an experience. This interpretation of the ongoing neural activity complements research showing that hippocampal lesions impair the ability to monitor recent choices [15,16,50] and to track events across time [11,13,14,20]. …”
Section: Resultssupporting
confidence: 63%
“…However, it is critical to note that these studies mark the few examples of hippocampal-dependent spatial cognition. Importantly, processing positional information alone does not seem to rely on the hippocampus [14,1820] particularly when it can be egocentrically defined from the perspective of the stationary monkey [21]. Instead, the hippocampus seems to be required when spatial relationships between objects in allocentric space must be formed, and when spatially-distinct objects must be linked across time.…”
Section: Hippocampal Dependence In Spatial Tasksmentioning
confidence: 99%
“…Hirsch & Segal, 1972;O'Keefe et al, 1975;Walker & Olton, 1979;Markowska et al, 1989;Murray et al, 1989;Aggleton et al, 1992;Gaffan, 1994;Ennaceur et al, 1996;Ennaceur & Aggleton, 1997;Parker & Gaffan, 1997;Whishaw & Tomie, 1997;Bussey et al, 2000;De Bruin et al, 2001;Easton et al, 2002;Buckley et al, 2004 andKwok, 2006;Kwok & Buckley, 2010;Kwok et al, 2015;Hodgetts et al, 2017Hodgetts et al, , 2018 Traditional Episodic Memory Tasks, e.g. WMS, CVLT, etc.…”
Section: Trace and Contextual Fear Conditioningmentioning
confidence: 99%
“…Additionally, the fornix is associated with recollection and recall in MRI studies (Rudebeck et al, 2009;Metzler-Baddeley et al, 2011) and has shown changes in patients with hippocampal lesions (Henson et al, 2016). Interestingly, causal evidence from humans and nonhuman primates further shows that transecting the UF or the fornix impairs cognitive performance in learning and memory tasks (D'Esposito et al, 1995;Aggleton et al, 2000;Gaffan, 2002;Browning and Gaffan, 2008;Tsivilis et al, 2008;Kwok et al, 2015). However, it remains unclear how learning new visuospatial information alters (sub)cortical connectivity, and how, following the loss of subcortical inputs to the cortex, this connectivity is rearranged.…”
Section: Introductionmentioning
confidence: 99%